Poets on the Psalms - Domina, Lynn (Trinity University Press, 2008)
"This collection of essays interprets the Psalms as poetry. Written by fourteen acclaimed poets, the essays approach the Psalms from a personal, often autobiographical perspective"--Provided by publisher.